E-Learning On Three Phase AC Induction Motor - Zuraidah, Yahya (UTeM, 2009)
Lesson and learning system very important in produce quality of student who capable of receiving learning outcome effectively. In live technological progress by today, E-Leaming's system has reach one important level in development of the country's education or countries outside. E-Ieaming services have evolved since computers were first used in education. E-Leaming lessons are generally designed to guide students through information or to help students perform in specific tasks. Three Phase AC Induction Motor learning's project objective based on this E-Leaming's system would be to facilitate students cottoned on to Three Phase AC Induction Motor with easier to understand. E-Leaming's module which operate in this project is had used Macromedia Flash's software 8.0. By using that software, system based on concepts interactive can produce and have one colourful design at making student have been interesting to use this module. Generally, this module is divided by several chapters to facilitate students understanding of each chapter effectively.